THE 16TH CENTURY SHAKESPEAREAN PLAY BROUGHT INTO THE 20TH CENTURY KERALA - Athira s; Devi K (International Journal of Psychosocial Rehabilitation, 2020)
To re-explore the Shakespearean plays in the malayalam movies. The 16th century situations and the time brought into 20th century Kerala. Malayalam movies and the industry have best explored the potentiality of cinematic version of Shakespearean plays. Both the movies ‘Kannaki’ and ‘Kaliyattam’ shows the main unveiling of Shakespearean plays ‘Othello’ and ‘Antony and Cleopatra’. Exhibiting the resemblances and the backdrop changes along with the time period. 16th century cultures,peoples mind change and how much difference it took,when it was interpreted on 20th century.